How do you use the binomial theorem to expand and simplify the expression #(a+6)^4#?

1 Answer
Aug 27, 2017

Answer:

#a^4 + 24a^3 + 216a^2 + 864a + 1296#

Explanation:

The binomial theorem states that

#(a+b)^n = ((n),(0)) a^n b^0 + ((n),(1)) a^(n-1) b^1 + ((n),(2)) a^(n-2) b^2 + ... + ((n),(n)) a^0 b^n#

#((n),(r))# is a combination read as "#n# choose #r#".

#((n),(r)) = color(white)I_nC_r = (n!) / (r! (n-r)!)#

To expand #(a+6)^4#, substitute #a=a, b=6,# and #n=4# into the formula.

#(a+6)^4 = ((4),(0)) * a^4 * 6^0 +((4),(1)) * a^3 * 6^1 + ((4),(2)) * a^2 * 6^2 + ((4),(3)) * a^1 * 6^3 + ((4),(4)) * a^0 * 6^4 #

#=1 * a^4 * 1 + 4 * a^3 * 6 + 6 * a^2 * 36 + 4 * a^1 * 216 + 1 * 1 * 1296#

#=a^4 + 24a^3 + 216a^2 + 864a + 1296#